Pengaruh Faktor- Faktor Ekonomi Terhadap Pengangguran Terbuka di Provinsi Sumatra Barat - Putri Lumban Toruan; Gita Manalu; Martina Br Sinaga; Hidayatullah Dayat (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
This research aims to analyze the influence of economic factors on the open unemployment rate in West Sumatra. Using panel data from 2013-2023, the analysis results show that labor force growth can lead to an increase in unemployment, especially if it is not balanced by adequate job creation. In contrast, domestic investment is shown to have a significant negative effect, supporting the theory that investment can reduce unemployment by expanding employment opportunities. However, economic growth and government expenditure did not significantly affect unemployment, suggesting that economic growth in West Sumatra was not labor-intensive enough to absorb the existing labor force. Future research should use longitudinal analysis with a longer period and qualitative methods to better understand the factors that influence unemployment. It is also important to consider other variables, such as education and labor skills, and to conduct case studies in specific regions to understand local dynamics. This study has limitations, including the use of secondary data that may not be fully accurate, unmeasured variables such as social and cultural conditions, and a geographical focus limited to West Sumatra province. Nevertheless, this research provides valuable insights and there is still much room for further exploration in understanding and addressing the issue of unemployment.